The phenomenon of ostracism in the system of transcendental concepts of life form - Nazarevich, Viktoriya (Psychological Prospects Journal, 2019)
In the article, the authors make an attempt to determine the features of the phenomenon of social isolation in the system of fundamental concepts and systematize the socio-psychological, philosophical ideas about alienation as a mechanism of ostracization in the group. Special attention is paid to the consideration of the personality system as a whole, autonomous from the nature of education, which functions according to its own specific social laws, and from the point of view of the identification of the personality as part of a more complex whole.The article is devoted to the importance of analyzing the basic transcendental factors of life form that influence the course of personal life of individuals and social groups, the primary factor of existential needs, which is most clearly manifested in the social interaction of the individual when she creates something fundamentally new from birth. In this case, quite often, without realizing, the regularity and motives of their actions, reactions, behavioral scenarios.The features of the reflexive reactions and responses of the individual to ostracism, such as: disinterest, criticism, prejudice, avoidance, rejection, betrayal, stigmatization, neglect, abandonment, resentment, intimidation, are highlighted. And various minor insults, and insults that have a general impact on emotions, self-esteem and behavior.The role of social status, self-esteem of personality, social affiliation, and characteristic features of endogenous factors, which can cause the risk that an unaccepted person maneuvers because of his distorted perception in a situation where the way out of isolation using its own capabilities is practically is impossible.The conclusions are made in the system of consideration of the concept of ostracism, that at the deep cognitive-emotional level it influences the actual fundamental situation of the personality, violating the satisfaction of the basic features of the transcendental concepts of the life form.Further consideration of this problem is provided in a more detailed study of the effect of ostracism on other fundamental categories of life form. And the study of individual personality traits that affect the departure of the individual, who is a discharge, from social exclusion.